历史的守秘者 ：马家辉《龙头凤尾》对香港故事的重述 = Keeping the secret : Ma Ka-fai’s once upon a time in Hong Kong as a narrative of Hong Kong - 林俊良 Lim, Chun Lean (2018)
马家辉《龙头凤尾》讲述河石镇青年陆南才南下香港闯荡的故事。身处乱离年代，陆南才从人力车夫发迹成为帮会堂主，私底下也与殖民情报官张迪臣展开秘密恋情。题材广涉殖民历史、战争离乱、会党轶事、同性恋爱、嫖赌饮吹，然而情节与文字皆敷衍得不腥不骚，呈示香港历史的横切面。通篇小说以“秘密”贯穿始末，每个人皆有各自的隐衷，在乱世里背负着各自的混乱，与香港文化和香港人自成隐喻，道出其守秘者、共谋者、背叛者的文化性格。在马家辉的笔下，香港沦陷史不外是一部人性史，他勾勒出历史的龙头与凤尾，也来回了香港的前世与今生。In Once Upon A Time in Hong Kong, Ma Ka-fai narrated the stories of Lu Nan-cai, a young man from Heshi Town, who is going southwards into Hong Kong. Living in the time of war, Lu became a gang master from the rickshaw driver gradually, he also privately started a secret love relationship with colonial intelligence officer David Morrison. The novel is writing within a wide range of topics related to colonial history, war time, secret society, homosexual love, gambling and prostitution, yet the plots and words are unconstrained and expressed the cross-section of Hong Kong history. The keyword “secret” is appearing throughout the whole novel. In those trouble time, everyone had their own secret and burdened with their own chaos, these formed the metaphor for current Hong Kong culture and Hong Kong people as well. Particularly, it indicated the three cultural characteristic of Hong Kong: the secret keeper, the collaborator, the betrayer. In Ma’s writing, the history of fallen Hong Kong is nothing more than a history of human nature. Ma leaded us to revisit the history, and reviewed the present and the past of Hong Kong.